Dual of Modulation Spaces with Variable Smoothness and Integrability. (29th May 2022) - Zhu, Hua
Abstract : In this article, we first give a proof for the denseness of the Schwartz class in the modulation spaces with variable smoothness and integrability. Then, we study the dual spaces of such modulation spaces.